The effect of the last glacial age on speciation and population genetic structure of the endangered Ethiopian wolf (Canis simensis). - Gottelli, D; Marino, J; Sillero-Zubiri, C; Funk, S (2004)
During the last glacial age, Afro-alpine habitats were widespread across the highlands of Ethiopia. A wolf-like canid ancestor is thought to have colonized this expanding habitat and given rise to a new species that was remarkably well adapted to the high altitude environment: the Ethiopian wolf Canis simensis. Here, we address the timing of genetic divergence and examine population genetic history and structure by investigating the distribution of mitochondrial DNA (mtDNA) sequence variation. The pattern of mtDNA variation and geographical distribution indicate an initial population expansion, probably immediately after divergence from the wolf-like ancestor, around 100,000 years ago. The partition of mtDNA haplotypes that followed was most likely the result of habitat reduction and fragmentation at the onset of deglaciation approximately 15,000 years ago. Phylogenetic and geographical associations suggest that the most likely genetic partitioning corresponds to three mountain areas, Arsi/Bale, Wollo/Shoa and Simien/Mt. Guna. Although there is a degree of clustering of haplotypes from both sides of the Rift Valley, the lack of reciprocal monophyly does not support the taxonomic classification of two subspecies. This study highlights the importance of populations north of the Rift Valley for the maintenance of genetic variability within the species and has consequent implications for conservation.